The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.21236/ada495182
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Issues Related to Advanced Cockpit Displays: Supporting the Transition between Internal and External Guidance

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…However, Prinzel et al (2006) demonstrated that 3D presentation in conjunction with 2D displays provided an increase in situational awareness and allowed pilots to avoid certain hazardous terrain [22]. Lohrenz (2003) demonstrated that performance and workload are optimal when the cockpit displays were of the simplest design and contained only the necessary information required [23].…”
Section: Figure 16 Pilot's Display Preference Based On Maneuver Typementioning
confidence: 99%
“…However, Prinzel et al (2006) demonstrated that 3D presentation in conjunction with 2D displays provided an increase in situational awareness and allowed pilots to avoid certain hazardous terrain [22]. Lohrenz (2003) demonstrated that performance and workload are optimal when the cockpit displays were of the simplest design and contained only the necessary information required [23].…”
Section: Figure 16 Pilot's Display Preference Based On Maneuver Typementioning
confidence: 99%
“…Course deviation. Course deviation was assessed by calculating the cross-track error, or XTE (Lohrenz, 2003). The XTE is the perpendicular distance between the participants' planned route and the actual track from the simulator GPS receiver.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…Overlaid versus separate databases for focused tasks. An analysis of data from the aviation and military domains reveals that performance time increases with overlaid display formats when used for focused attention tasks (Kroft & Wickens, 2001;Lohrenz, 2003;Wickens, Kroft, & Yeh, 2000). Kroft and Wickens (2001) measured reaction times of student pilots to questions related to one of two overlaid databases on a "small integrated display"; one domain consisted of navigational ground features (e.g., roads, power lines, bridges), and the other consisted of air hazards (a composite display of weather and air traffic) ( Figure A4).…”
Section: Background Clutter Complexitymentioning
confidence: 99%
“…Overlaid and separate display formats; displays used in an experiment by Kroft and Wickens (2001). In a low-fidelity simulation, Lohrenz (2003) also examined the effects of display overlay by measuring target acquisition times by participants with either a pilot's license or flight simulator experience, for targets in a military aviation environment.…”
Section: Background Clutter Complexitymentioning
confidence: 99%
See 1 more Smart Citation